FAMILY DYNAMICS THROUGH DISCOURSE ANALYSIS IN ‘HOW TO MAKE MILLIONS BEFORE GRANDMA DIES’ MOVIE - Salsabil Putri Setiawan; Nurul Nabila Lubis, Grace Fanesya Ginting, Efani Margareth Ginting (Adisam Publisher, 2024)
This study applies Fairclough’s Critical Discourse Analysis (CDA) to explore the complex interplay of economic struggles, inheritance dynamics, and societal expectations within familial relationships as depicted in the movie ‘How to Make Millions Before Grandma Dies.’ Through a qualitative examination of characters’ dialogues and actions, the analysis reveals how economic pressures profoundly impact family dynamics, often leading to conflicts driven by financial necessity over traditional values of filial piety. The discourse on inheritance further illuminates entrenched gender biases, highlighting the preference for male heirs in the distribution of familial wealth and property. Fairclough's framework facilitates a nuanced understanding of power dynamics embedded in these discourses, emphasizing their role in shaping identities and relationships within the family unit. This research contributes insights into the broader implications for familial cohesion and societal norms, underscoring the challenges posed by economic inequalities and the evolving nature of familial roles in contemporary contexts.